Decoupled Speed and Torque Control of IPMSM Drives Using a Novel Load Torque Estimator - ZAKY, M. (Advances in Electrical and Computer Engineering, 2017)
This paper proposes decoupled speed and torque control of interior permanent magnet synchronous motor (IPMSM) drives using a novel load torque estimator (LTE). The proposed LTE is applied for computing a load torque and yielding a feed-forward value in the speed controller to separate the torque control from the speed control. Indirect flux weakening using direct current component is obtained for high speed operation of the IPMSM drive, and its value for maximum torque per ampere (MTPA) control in constant torque region is also used. LTE uses values of direct and quadrature currents to improve the behavior of the speed controller under the reference tracking and torque disturbances. The complete IPMSM drive by Matlab/Simulink is built. The effectiveness of the proposed control scheme using an experimental setup of the complete drive system implemented on a DSP-DS1102 control board is confirmed. Extensive results over a wide speed range are verified. The efficacy of the proposed method is confirmed in comparison to a conventional PI controller under both the reference speed tracking and load torque disturbance.